Forest fire risk assessment model using Remote sensing and GIS techniques in Tujiin nars national park, Mongolia (Proceedings of the Mongolian Academy of Sciences, 2021)
Forest is an important natural resource that should be carefully protected and rationally managed. In recent years, deforestation and forest land degradation have become the main concern for forest specialists as well as policy and decision-makers dealing with environment issues. It has been found that much of the existing forests have been destroyed, mainly by shifting cultivation, timber preparation, legal and illegal logging, and forest fires. To protect and conserve the deteriorating forest, it is very important to conduct forest-related risk assessment and map the outcomes in a spatial domain. The aim of this research is to conduct a forest fire risk assessment mapping of Tujiin Nars National Park using geographic information system (GIS) and remote sensing (RS) techniques. The research approach is based on an empirical model. It includes three parameters (i.e. geomorphology, vegetation cover combustibility and human activity) that are crucial for the forest fire assessment. The results of the study can be used for different decision making processes.